Measuring Health-Related Quality of Life in Strabismus: A Modification of the Adult Strabismus-20 (AS-20) Questionnaire Using Rasch Analysis. - Vijaya K Gothwal; Seelam Bharani; Ramesh Kekunnaya; PreetiPatil Chhablani; Virender Sachdeva; Niranjan K Pehere; Asa Narasaiah; Rekha Gunturu (PLoS ONE, 2015)
To evaluate the psychometric properties of the Adult Strabismus-20 (AS-20)- a health-related quality of life (HRQoL) questionnaire in adults with strabismus, and if flawed, to revise the AS-20 and its subscales creating valid measurement scales.584 adults (meanage, 27.5 years) with strabismus were recruited from an outpatient clinic at a South Indian tertiary eye care centre and were administered the AS-20 questionnaire.The AS-20 was translated and back translated into two Indian languages. The AS-20 and its two 10-item subscales - 'psychosocial' and 'function'were assessed separately for fit to the Rasch model, including an assessment of the rating scale, unidimensionality (by principal components analysis), measurement precision by person separation reliability, PSR, targeting, and differential item functioning (DIF; notable > 1.0 logits).Response categories were not used as intended, thereby, required re-organization and reducing their number from 5 to 3. The AS-20 had adequate measurement precision (PSR = 0.87) but lacked unidimensionality; however, deletion of the six multi-dimensionality causing items and an additional three misfitting items resulted in 11-item unidimensional questionnaire (AS-11). Two items failed to satisfy the model expectations in the 'psychosocial' subscale and were deleted - resulting in an 8-item unidimensional scale with adequate PSR (0.81) and targeting (0.23 logits). One item misfit in the 'function' subscale and was deleted-resulting in a 9 item Rasch-revised unidimensional subscale with acceptable PSR (0.80) and targeting (0.97 logits).None of the items displayed notable DIF by age, gender and level of education.The AS-11 and its two Rasch-revised subscales - 8-item psychosocial and 9-item function subscale may be more appropriate than the original AS-20 and its two 10-item subscales for use as unidimensional measures of HRQoL in adults with strabismus in India. Further work is required to establish the validity of the revised rating scale.